KEARIFAN LOKAL BALI DALAM MEMBANGUN KARAKTER SISWA SEKOLAH DASAR - Ni Ketut Erna Muliastrini; I Gusti Ayu Adi Rahayuni (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
The purpose of this study is to convey thoughts about the role of Balinese local wisdom in developing character education. Indonesia, which is currently experiencing a degradation of character values as shown by the low manners of teenagers, brawls, cheating culture and the behavior of corrupt officials, illustrates that implementing good education in schools, families and communities does not build the character of this nation. To overcome this problem, one way that can be done is to explore the national character, especially the integration of local Balinese wisdom in implementing education in schools. (a) Local wisdom integrated into character education is: (1) Tumpek Uduh, (2) Tumpek Kandang, (3) tattwan asi, (4) subak, (5) salunglung sebaya taka, (6) asta kosala-kosali, (7) Shanti greetings, (8) Nyepi Day, (9) ngopin, (10) medelokan, (11) resik, (12) menyama beraya, (13) eling, (14) swadharma, and (15) other cultures. (b) Balinese local wisdom can be integrated into character education by: (1) integrating in building school culture, (2) integrating in building class culture, and (3) integrating in learning, both in carrying out education and promoting Balinese culture that appropriate or relevant to the subject matter in learning.Keywords: Character, Balinese Local Wisdom, Elementary School Students